Digital Fun Thinkers Media to Improve Social Science Learning Outcomes for 4th Grade Elementary School Students - Putu Stephanie Adriana Mertha; I Gusti Ayu Tri; Jianbang Deng (Jurnal Media dan Teknologi Pendidikan, 2025)
Low learning outcomes in Natural and Social Sciences (IPAS) remain a persistent issue in elementary education. This problem often arises from the dominance of conventional teaching methods and the limited use of digital media that foster active student engagement. This study aims to analyze the development process and examine the validity, practicality, and effectiveness of the Fun Thinkers Digital learning media based on the Smart Apps Creator 3 application to enhance students’ learning outcomes. This research employed a Research and Development (R&D) approach using the ADDIE model, involving subject-matter experts, media experts, teachers, and elementary school students as participants. Data were collected through observation, interviews, questionnaires, and learning tests, then analyzed descriptively and inferentially. The results reveal that Fun Thinkers Digital demonstrates a very high level of feasibility, is considered practical for classroom use, and effectively improves students’ conceptual understanding and learning motivation. These findings indicate that integrating interactive digital media can serve as a strategic innovation in IPAS learning to create meaningful, engaging, and context-based learning experiences aligned with the demands of 21st-century education.